(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The article analyzes the role of the Islamic financial instrument - sukuk - in financing sustainable development goals. In recent years, due to climate change, increasing debt burden and social inequality in the world economy, the need for innovative, fair and Sharia-compliant financial mechanisms to ensure sustainable development has increased. As one of such instruments, sukuk is used in the areas of infrastructure, energy, education, social protection and ecology. The article examines the role, advantages and prospects of sukuk in achieving the Sustainable Development Goals.